Impact of COVID-19 on growth hormone therapy efficacy in pediatric patients with short stature - Yoo-Mi Kim; Ah-Reum Oh; Heon-Seok Han; Jeesuk Yu; Jaehong Yu; Tae Kwan Lee; Gyung Min Lee; Jaewon Choe; Jun Suk Oh; Han Hyuk Lim (Endocrine Connections)
The coronavirus disease (COVID-19) pandemic has affected global healthcare and raised concerns about growth hormone (GH) therapy outcomes in pediatric patients with short stature. This study compared GH therapy efficacy and outcomes before and during the pandemic. We retrospectively analyzed 2,827 pediatric patients with idiopathic GH deficiency, short stature in children born small for gestational age (SGA), Turner syndrome (TS), or idiopathic short stature (ISS) from the LG Growth Study, categorized into pre-pandemic (February 2017–January 2020, n = 1,612) and pandemic (February 2020–January 2023, n = 1,215) groups. The key outcomes included height standard deviation score (SDS), body mass index (BMI)-SDS, insulin-like growth factor 1 levels, and adverse events. Significant differences were observed between groups. During the pandemic, the proportion of SGA and TS decreased, whereas that of ISS increased. IGF-1 and total cholesterol levels were higher in the early treatment phase of the pandemic but tended to normalize over time. Reported adverse events were markedly lower during the pandemic, particularly infectious and systemic complications. GH therapy remained effective during the pandemic despite healthcare disruptions. Pandemic-related shifts in BMI, IGF-1, and adverse event reports suggest environmental influences on treatment patterns. These findings underscore the importance of monitoring chronic pediatric care under changing public health conditions.